answersLogoWhite

0


Best Answer

Transitive Property

That's called the transitive property.

User Avatar

Wiki User

โˆ™ 2013-08-20 23:57:59
This answer is:
User Avatar
Study guides

Data Science

โžก๏ธ
See all cards
4.29
โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…
7 Reviews

Add your answer:

Earn +20 pts
Q: What property states if a equals b and b equals c then a equals c?
Write your answer...
Submit
Still have questions?
magnify glass
imp
Related questions

Who stated if a equals b and b equals c then a equals c?

by transitive property


What is the property that states if a b and b c then a c?

a=b and b=c then a=c is the transitive property of equality.


What is a distributive property?

The distributive property states that: a(b + c) = a×b + a×c


What is the formula called a equals b b equals c therefore a equals c?

The Transitive Property of Equality.


What does a distributive property mean?

The distributive property states that a × (b + c) = a × b + a × c


If a equals b and b equals c how to proof that a equals c?

The transitive property of equality says that if a=b, then b=c.If a=b and b=c, then a=cTo Prove:Using the equation:a=bsubstituting the value of b in terms of c:which is: b=ctherefore:a=ba=(c)a=c


What property states that if a b and b c then ac?

transitive


What is the formula called a equals b b equals c therefore a?

That is not a formula, it is the transitive property of equality.


What is the distributive property for multiplication?

The distributive property of multiplication over addition states that a*(b + c) = a*b + a*c


What does distributive porperty means?

The distributive property states that a × (b + c) = a × b + a × c


What is the definition of distributive property?

The DISTRIBUTIVE property is a property of multiplication over addition (OR subtraction). In symbolic terms, it states that a * (b + c) = a * b + a * c


What is the definition of Distribution Property?

The DISTRIBUTIVE property is a property of multiplication over addition (OR subtraction). In symbolic terms, it states that a * (b + c) = a * b + a * c

People also asked